Becoming father negatively affects professional road cycling performance - Anke Baetens; Jeroen Belien; Filip Van den Bossche (Cogent Social Sciences, 2024)
This study examines the impact of becoming father on the performance of professional road cyclists. Fixed effects panel regression is used to compare cycling performance over a period after having a child with the performance in the same period the year before. The sample includes 299 professional male road cyclists who had one or more children between 2001 and 2019, with a total of 496 children. After correcting for personal and team related factors, cycling performance is significantly lower after the birth of a child. This is a first indication that having a child can influence the performance of professional athletes in a negative way. The results of this study may help to provide better psychological and athletic support for recent fathers, and are potentially relevant to contexts other than professional (cycling) sport.